Differentiation of Real Estate Market in Istanbul between 1995, 2005 - Funda Yirmibesoglu (European Regional Science Association (ERSA), 2005)
Due to migration and rapidly increasing urban population settlement in urban land, lacking any planning or infrastructure, in addition to the destruction of the 17th August 1999 earthquake, it is necessary to examine uncertainty of housing demand and supply in Istanbul. After the 17th August earthquake, Istanbul has been adversely affected economically and socially. Significant differentiation in urban housing demand and supply has been observed. In the paper, this differentiation will be scrutinized for the 1995-2005 period before the earthquake, and the period after the earthquake until present. The distribution of real estate agencies will be examined with the help of GIS and the changes in the real estate market with questionnaires. The purpose of the research is to analyse; Housing production in the housing market in Istanbul; Differentiation of housing demand and supply; Distribution of real estate agencies; Differentiation of housing value and land value in neighbourhoods before and after the earthquake. The study provides an insight into the housing and real estate market in Istanbul, results and proposals of which will be presented.
Keywords: 330